SARS-CoV-2(COVID-19) - Galib, Batool Ali (Journal of the Faculty of Medicine Baghdad, 2020)
Coronaviruses are a large family of viruses which may cause illness in animals or humans.  In humans, seven strains of coronaviruses were recognized to cause respiratory infections ranging from the common cold associated with HKU1, NL63, OC43 and 229E viruses to more severe diseases such as Severe Acute Respiratory Syndrome (SARS) during 2002, Middle East Respiratory Syndrome (MERS) during 2012, and the COVID-19 that started during December 2019 in Wuhan, China.This is a review for the current pandemic